Synergy and Prediction in the Strategy of Mergers and Acquisitions - Mesjasz, Czesław; Szarucki, Marek (Studia Oeconomica Posnaniensia, 2017)
Whatever could be the nature of the motivations and objectives of mergers and acquisitions, their goal is to achieve synergy, which is one of the basic characteristics of complex systems related to the effect of emerging properties. In the theory and practice of mergers and acquisitions, the term "synergy" is an important analytical term but also, too often, it is a slogan repeated without deeper reflection by practitioners and theorists. Due to the complexity of the processes of mergers and acquisitions, and due to the links between complexity and ignorance, the identification of potential synergies in the developing strategy of mergers and acquisitions is associated not only with the aim to increase knowledge but also to identify a lack of knowledge. The aim of the article is to provide an initial response to the question to what extent the identification of emerging, unknown effects of mergers and acquisitions that make up their synergy, is associated with the lack of knowledge (ignorance) of decision makers in the process of developing the strategy.